Colonial Bank, Port of Spain - Trinidad - (:unkn) unknown (Goodwille and Wilson Ltd., Trinidad, 2009)
Photo depicting the exterior view of the bank with louvered windows and arched shaped spaces above them. There is a horse, carriage and driver in the roadway. A partial view of a tall tree and bicycle is also visible.
Colour: Black and White; Style: Landscape : Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Banks and banking--Trinidad and Tobago; Public buildings--Trinidad and Tobago; 1908; Architecture--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago